The dependence ofthe crystallite sizeof ZnS and CdS,obtainedby the hy-drothermal method, on the synthesis temperature - Abdullin, Kh A.; Gabdullin, M. T.; Migunova, A. N.; Podrezova, L. V. (Recent Contributions to Physics, 2013)
Samples of zinc sulphide (ZnS) and cadmium sulphide (CdS) were synthesized by a hydrothermal method from water solutions of precursors both in volume and on a substrate. The morphology of thesynthesized ZnS and CdS samples was investigated by scanning electronic microscopy in dependence on technological conditions of synthesis. The study showedthat the surface ofZnSnanospheres has asmooth structure. ZnS sphereswith sizesof 300-400 nmwere synthesizedon the substrate surface. Larger andpartiallyconglomerated ZnS sphereswere obtained bythe formation of ZnS particlesin the volumeofthe solution andsubsequentdepositionon the substrate. CdS particles have an irregular shape, and the elementalcomposition of the sampleswas closeto the stoichiometric. The crystal structure of the received sample was investigated by X-ray diffraction. It is found that the ZnS was obtained as cubic symmetry (sphalerite) nanocrystals and CdS was obtained as cubic and hexagonalsymmetry nanocrystals. ZnS crystallite sizeincreases monotonicallywith increasing temperatureof synthesis,so the temperature is a convenientparameterto control the sizeof nanocrystallitesin the rangeof 2 to 100 nm.
Keywords: ZnSandCdSnanocrystallites; hydrothermal way; conditions of synthesis; X-ray analysis